The relationship between the morphological structure and the ecological niche occupied by cereals and sedges in Alpine lichen tundra northwest Caucasus - N. V. Lyubeznova (Проблемы ботаники Южной Сибири и Монголии, 2020)
The relationship between the life form and distribution of cereals, sedges and Lusula spicata (L.) DC. in theAlpine lichen tundra association was revealed. The dependence of plants to forms of relief and certain ecological nicheswas studied. Within the framework of the carousel model (van der Maarel, Sykes, 1993) their occurrence and the speedof the small-scale turnover in the community were estimated.